2010
DOI: 10.1097/prs.0b013e3181d5132a
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Palate Repair with Delayed Hard Palate Closure Is Related to Favorable Maxillary Growth in Unilateral Cleft Lip and Palate

Abstract: The data suggest that in patients with unilateral cleft lip and palate, two-stage palate repair has a smaller adverse effect than one-stage palate repair on the growth of the maxilla. This stage effect is on the anteroposterior development of the maxilla and is attributable to the development being undisturbed before closure of the hard palate (i.e., hard palate repair timing specific).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 24 publications
(31 reference statements)
3
35
1
5
Order By: Relevance
“…As median facial dysplasia patients mature, their midface growth slows and the profile becomes more concave. This growth pattern predicts a possible need for orthognathic surgery in 95%, which is significantly higher than the 14-60% rate reported for nonsyndromic patients with repaired clefts of the lip and palate 2,4,7,12,13 .…”
Section: Discussionmentioning
confidence: 73%
“…As median facial dysplasia patients mature, their midface growth slows and the profile becomes more concave. This growth pattern predicts a possible need for orthognathic surgery in 95%, which is significantly higher than the 14-60% rate reported for nonsyndromic patients with repaired clefts of the lip and palate 2,4,7,12,13 .…”
Section: Discussionmentioning
confidence: 73%
“…This is in direct contrast to the work of Williams et al [25] who previously reported that high-volume surgeons achieved good speech outcome. The explanation for the discrepant results is unclear, although several additional studies have failed to find a relationship between the dental arch relationship and the volume of unilateral cleft lip and palate repairs undertaken by the surgeon [26][27][28]. Whether this relates to difficulty of case mix (i.e., the experienced surgeons had been assigned the difficult cases), sample size, or other variables is unclear at this time.…”
Section: Discussionmentioning
confidence: 95%
“…Infants sleeping in prone position could reduce cleft size [31]. Previous studies also showed that a later palate repair results in favorable maxillary growth because possible interference with maxillary growth is postponed to a later age when less growth remains [27,28,[32][33][34] and that a staged palatal closure by starting closure of the soft palate with a posterior vomer flap incorporation may narrow the size of the remaining cleft spontaneously [35] or by starting closure of the hard palate with a single layer vomer flap may facilitate a smaller later palate repair [1].…”
Section: Discussionmentioning
confidence: 99%
“…This allows for the use of smaller flaps at the time of the hard palate repair 92 (Level V evidence). Studies have supported the use of a 2-stage procedure as it facilitates normal midfacial growth [93][94][95][96] (Level IV evidence). However, delayed hard palate closure has been associated with a higher incidence of velopharyngeal insufficiency and compensatory misarticulations 97 (Level IV evidence).…”
Section: One-stage Versus 2-stage (Schweckendiek) Palatementioning
confidence: 99%